Karaite Education in Crimea at the End of the 19th Century: An Unknown Resolution - Machcińska, Małgorzata (Karaite Archives, 2014)
The article is a contribution to studies of Karaite education in Eastern Europe. It presents an unknown resolution of the Taurida and Odessa Spiritual Consistory dated to 1898, which approved a new system of education in the Karaite communities of the Taurida and Odessa Spiritual Consistory. It was a formal act which approved the transformation of Karaite education, which was gradually taking place in the second half of the 19th century, and its permanent re-alignment in relation to the Russian education system of that time. This resolution is important as it contributed to a decline of the Hebrew language and Hebrew literature in the Karaite community.